2002-2012: 10 years of research progress in horizontal-axis marine current turbines - Ng K.-W.; Lam W.-H.; Ng K.-C. (MDPI AG, 2023)
Research in marine current energy, including tidal and ocean currents, has undergone significant growth in the past decade. The horizontal-axis marine current turbine is one of the machines used to harness marine current energy, which appears to be the most technologically and economically viable one at this stage. A number of large-scale marine current turbines rated at more than 1 MW have been deployed around the World. Parallel to the development of industry, academic research on horizontal-axis marine current turbines has also shown positive growth. This paper reviews previous research on horizontal-axis marine current turbines and provides a concise overview for future researchers who might be interested in horizontal-axis marine current turbines. The review covers several main aspects, such as: energy assessment, turbine design, wakes, generators, novel modifications and environmental impact. Future trends for research on horizontal-axis marine current turbines are also discussed. 2013 by the authors; licensee MDPI, Basel, Switzerland.